Establishing a core collection from the integration of morpho-agronomical, phytopathological and molecular data - Martins, Francielle Alline; Silva, Derly José Henriques da; Carneiro, Pedro Crescêncio Souza (Revista Ciência Agronômica, 2015)
The aim of this study was to establish and compare, as to their representativeness, core collections obtained from quantitative data, multicategoric, molecular and collections that covering all this information simultaneously. Ten subcollections were established from 67 tomato accessions of the Germplasm Bank of the Universidade Federal de Viçosa (BGH-UFV), characterized according to 19 quantitative traits, 30 multicategoric characters, 52 ISSR loci and to the reaction to three pathogens. These subcollections were defined by the combination of the nature of data collected and the sampling rate. The COD-20 subcollection stood out in 20% intensity of sampling by has higher rates of coincidence amplitude followed by more appropriate values of variance. At 30% intensity, subcollection MOL-30 was as efficient as the subcollection COD-30 when considering only the rates of coincidence of the amplitude and the variances. However, the graphical analysis of the variability showed a slight superiority of subcollection COD-30 in maintaining the variability, especially regarding multicategoric characters. So whenever data from different sources are available, should be prioritized the establishment of core collections from the integration of these data, since these were more representative when the amplitude coefficient, variance, and retention index of variability, are regarded simultaneously.

O objetivo deste estudo foi estabelecer e comparar, quanto à representatividade, coleções nucleares obtidas a partir de dados quantitativos, multicategóricos, moleculares e coleções que contemplem todas essas informações, simultaneamente. Foram estabelecidas 10 subcoleções a partir de 67 acessos de tomateiro do Banco de Germoplasma de Hortaliças da Universidade Federal de Viçosa (BGH-UFV), caracterizados quanto a 19 caracteres quantitativos, 30 multicategóricos, 52 locos ISSR e reação a três patógenos. Essas subcoleções foram definidas pela combinação entre a natureza dos dados avaliados e a intensidade de amostragem. A subcoleção COD-20 destacou-se a 20% de intensidade de amostragem por possuir maiores índices de coincidência da amplitude acompanhados de valores de variância mais adequados. A 30% de intensidade, a subcoleção MOL-30 foi tão eficiente quanto à subcoleção COD-30, quando se considerou apenas os índices de coincidência da amplitude e as variâncias. Entretanto, a análise gráfica da variabilidade mostrou uma ligeira superioridade da subcoleção COD-30 em manter a variabilidade, principalmente em relação aos caracteres multicategóricos. Assim, sempre que dados de diferentes naturezas estiverem disponíveis, deve-se priorizar o estabelecimento de coleções nucleares a partir da integração dos mesmos, uma vez que essas se mostraram mais representativas, quando considerados o coeficiente de amplitude, variância e o índice de retenção da variabilidade, simultaneamente.
Keywords: Retention rate variability; Amplitude coefficient; Germplasm; Variance